Pengaruh Biaya Promosi Dan Biaya Administrasi Umum Terhadap Laba Bersih Pada Perusahaan Manufaktur Sub Sektor Rokok Yangterdaftar di Bursa Efek Indonesia (BEI) Periode 2020—2024 - Khatimah, Nurul; Mulyana, Asep; Lesmana, Kusnadi Kibet; Januarharyono, Yudhaswara; Priatna, Ami (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the partial and simultaneous effects of Promotional Expenses and General Administrative Expenses on Net Profit in cigarette sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. A quantitative approach with descriptive and associative methods was applied using secondary data from the financial reports of PT Gudang Garam Tbk., PT Hanjaya Mandala Sampoerna Tbk., and PT Wismilak Inti Makmur Tbk. Data were analyzed using multiple linear regression, t-test, and F-test with IBM SPSS Statistics version 25. The results show that Promotional Expenses have a partial effect on Net Profit, while General Administrative Expenses do not. However, both variables simultaneously affect Net Profit.